Carpooling systems for commuting among teachers: an expert panel analysis of their barriers and incentives - Rey-Merchán, María del Carmen (2022)
Sustainable mobility is a current challenge in our society. Research shows that carpooling systems are potential solutions that could mitigate environmental pollution and urban congestion and provide cost savings for their users. Despite their potential benefits, the levels of carpooling practices among some occupations could be improved. Teachers are suitable for carpooling experiences due to their specific working conditions (e.g., timetables, destinations changes, path matches); however, there is no research solely focused on teachers. Thus, the current research aimed to analyze the barriers and incentives for teachers using carpooling systems for commuting. A panel member was selected following the staticized group technique. Panelists were surveyed to evaluate the advantages and disadvantages of carpooling. Results showed that fuel savings were considered by the expert panel as the most important incentive for carpooling. For short distances, carpooling was not considered the best commuting option. Additionally, the increase in travel time and loss of personal independence were identified as relevant barriers. Based on the opinions of experts, it can be concluded that carpooling barriers outweigh the incentives for the commuting of teachers. To promote carpooling practices, institutional mobility plans with advantages for carpoolers could improve the teachers’ perceptions about carpooling. Future carpooling strategies should consider these results to promote incentives and address the identified barriers.